Growing Teratoma Syndrome: A Rare Outcome - João Rebelo; Francisco Moreira; Margarida Morgado; Ana Sofia Preto; António Madureira (Case Reports in Urology)
Growing teratoma syndrome is a rare condition described in both testicular and ovarian cancer. We present a case of a 26-year-old male with known mixed germ cell tumor which exhibited new and progressive secondary lesions during imaging surveillance, later to be histologically characterized as teratomas.